Tap the sap – investigation of latex-bearing plants in the search of potential anticancer biopharmaceuticals - Mazur, Oliwia; Bałdysz, Sophia; Warowicka, Alicja; Nawrot, Robert (Frontiers in Plant Science, 2022)
Latex-bearing plants have been in the research spotlight for the past decades. Since ancient times their extracts have been used in folk medicine to treat illnesses. Currently they serve as promising candidates for molecules in cancer treatment. Up to date there have been several in vitro and in vivo studies related to the topic of cytotoxicity of extracts from latex-bearing plants towards various cell types. The number of clinical studies still remains scarce, however, the number is slowly increasing. To the best of our knowledge, the scientific community is still lacking in a recent review summarizing the research on the topic of cytotoxicity and anticancer activity of latex-bearing plant extracts. Therefore, the aim of this paper is to review the current knowledge on in vitro and in vivo studies, which focus on the cytotoxicity and anticancer activities of latex-bearing plants. The vast majority of the studies are in vitro, however, the interest in this topic resulted in the growth of the number of in vivo studies, leading to a promising number of plant species whose latex can potentially be tested in clinical trials. We have described the latex of several researched plant species, in some instances the effectiveness is compared to that induced by commonly used therapeutics currently available on the scientific market. The cytotoxic effect of the plant's crude latex, its fractions and isolated compounds is analyzed. The in vivo studies showed the effect of plant latex on the growth and volume of a tumor. Additionally, we present data regarding plant-mediated biosynthesis of nanoparticles, which is regarded as a new branch in plant latex research. We analyzed the cytotoxic effect of these particles on cells. Data regarding the cytotoxicity of such particles raises their potential to be involved in the design of novel cancer therapies. Throughout the course of this review we concluded that plant latex is a rich source of many compounds, which can be further investigated and applied in the design of anticancer pharmaceuticals. The comprehensive study of molecules from latex-bearing plants can result in finding a promising alternative to several drugs on the market.